Farmers Access, Adoption Behaviour and Constraints Analysis in Improved Technology Dissemination: A Case Study on System of Rice Intensification in Bihar (Indian Journal of Extension Education, 2017)
System of Rice Intensification (SRI) is an environment well disposed and novel strategy of rice cultivation which incorporates utilization of less seed, less water and fewer chemicals to obtain higher yield and profitability. A study was undertaken in Bihar to assess the extent of adoption of SRI and its determinants and constraints using primary data collected for the Agricultural Year 2013-14. Tabular analysis, Tobit regression, Garrett’s ranking were employed. Adoption index showed transplanting early seedling having highest weightage and poor adoption in all SRI practices. Tobit analysis indicated that access to extension and number of training attended has significant influences on adoption of SRI package of practices. Non- availability of skilled labour was found to be the major constraint in adoption of SRI method. To realize the inclusive and full benefit of SRI technology, the efforts should be directed to enhance the adoption of recommended practices of SRI by all the stakeholders, demonstration of SRI cultivation on farmers’ fields, training to farm labourers, standardize the SRI practices and mechanization of SRI operations.